Aktivitas Perangkap Radikal Bebas dan Penghambat α -Glucosidase pada Tanaman Obat: Free Radical Scavenging and α -Glucosidase inhibitory Activities of Selected Medicinal Plants - Sriwahyuni, Indah; Hariadi, Untung Slamet; Prasetyo, Rahadian Adi (Politeknik Pertanian Negeri Samarinda, 2023)
The leaf of five selected medicinal plants namely Mangifera indica, Muntingia calabura, Phaleria macrocarpa, Morinda citrifolia and Garcinia mangostana were investigated to determine their therapeutic potential to inhibit key enzymes in carbohydrate metabolism, which has relevance to the management of hyperglycemia and type 2 diabetes. The free radical scavenging activity was also assessed using DPPH assay. The studied plants exhibited varied free radical scavenging and α-glucosidase inhibition activities. The most potent antioxidant activity was demonstrated by M. indica extracted using 50 % ethanol with an IC50 value of 15.79±1.79 μg/mL. Both 50 and 100 % ethanol extracts of G. mangostana and 50% ethanol extract of M. calabura also showed strong antioxidant activity with IC50 values of 21.77 ± 6.97, 25.99± 1.37 and 36.90 ± 6.89 μg/mL, respectively. Of all the plants examined for α-glucosidase inhibition activity, M. calabura extracted with 50 % ethanol exhibited higher activity with IC50 value of 0.48±0.12 μg/mL. The results obtained in this study showed that M. indica leaves as the most potent antioxidant and could be suggested as a potential natural source of antioxidant compound. Meanwhile, M. calabura leaves have good potential for the management of hyperglycemia, diabetes and the related condition of oxidative stress.